2020
DOI: 10.1136/jitc-2020-001679
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase correlates with tumor immune activity and programmed death ligand-1 expression in Merkel cell carcinoma

Abstract: BackgroundMerkel cell carcinoma (MCC) is a rare and highly malignant skin cancer. Some cases have a good prognosis and spontaneous regression can occur. Reported prognostic markers, such as Merkel cell polyoma virus infection or programmed death ligand-1 (PD-L1) expression, remain insufficient for precisely estimating the vastly different patient outcomes. We performed RNA sequencing to evaluate the immune response and comprehensively estimate prognostic values of immunogenic factors in patients with MCC.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In addition, the G6PD-NADPH redox system was shown to be important for stabilizing the metabolism of T cells and regulating antitumor immunity ( Gu et al, 2021 ). It was reported as a prognostic marker to predict the immunotherapy response of Merkel cell carcinoma ( Nakamura et al, 2020 ). For tumor protein p53 inducible protein 3 ( TP53I3 ), it functions as reactive oxygen species and involves in DNA damage response pathway ( Kotsinas et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the G6PD-NADPH redox system was shown to be important for stabilizing the metabolism of T cells and regulating antitumor immunity ( Gu et al, 2021 ). It was reported as a prognostic marker to predict the immunotherapy response of Merkel cell carcinoma ( Nakamura et al, 2020 ). For tumor protein p53 inducible protein 3 ( TP53I3 ), it functions as reactive oxygen species and involves in DNA damage response pathway ( Kotsinas et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, based on the RNA sequencing results, G6PD was significantly upregulated in MCPyV-negative/TLS-negative samples. Glucose-6-phosphate dehydrogenase (G6PD) is a factor that we previously reported as a promising prognostic and immune activity biomarker in MCC ( 15 ). Thus, in the present study using the same cohort, G6PD was highly expressed, indicating a poor prognosis as well as low immune activity in this group.…”
Section: Discussionmentioning
confidence: 99%
“…The first step of the pentose phosphate pathway (PPP) is catalyzed by the G6PD enzyme. A relatively high number of studies have interrogated the role of G6PD in different cancer types but how the overexpression of G6PD contributes to the development of different tumors is largely unknown ( 82 ). Yang HC et al in a very recent study have demonstrated that deregulated G6PD status and oxidative stress are highly related and are involved in cancer progression ( 83 ).…”
Section: Glucose Metabolismmentioning
confidence: 99%